Political reservation and female empowerment: evidence from Maharashtra, India. (2nd October 2017) - Priebe, Jan
Abstract: This paper studies the impact of political reservation for women on political participation and empowerment of women living in areas where gender quotas are mandated. Following the 1992 passage of the 73rd Constitutional Amendment in India, one-third of village government head positions are reserved for women. Utilizing the random allocation of reserved seats and a unique individual level data-set which captures a large set of measures on political participation of women, we find that women residing in areas with a female village government head show significantly higher levels of political participation and empowerment. Overall, the observed effect can be entirely attributed to improved outcomes of women from a lower socio-economic strata, while no effect is found for economically better-off women. The results suggest that the imposed gender quotas are an effective means of overcoming inequalities and contributed to giving disadvantaged women more voice and opportunity for political empowerment. We further investigate the role that the level of women's political participation plays on the type and quality of public services delivered. Our results indicate that the level of women's political participation and empowerment is an important channel through which public service delivery is influenced.